2016
DOI: 10.1590/1678-4685-gmb-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of WUSCHEL-related homeobox (WOX) genes to identify the phylogenetic relationships among Petunia species

Abstract: Developmental genes are believed to contribute to major changes during plant evolution, from infrageneric to higher levels. Due to their putative high sequence conservation, developmental genes are rarely used as molecular markers, and few studies including these sequences at low taxonomic levels exist. WUSCHEL-related homeobox genes (WOX) are transcription factors exclusively present in plants and are involved in developmental processes. In this study, we characterized the infrageneric genetic variation of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(72 reference statements)
0
9
0
1
Order By: Relevance
“…The ecological and/or environmental factors responsible for this isolation remain to be determined. Despite morphological similarities, phylogenetic analyses [ 24 , 25 ] found that P. bajeensis is not closely related to the remaining taxa of the complex; it is the sister species of the highland subclade in the short corolla tube clade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ecological and/or environmental factors responsible for this isolation remain to be determined. Despite morphological similarities, phylogenetic analyses [ 24 , 25 ] found that P. bajeensis is not closely related to the remaining taxa of the complex; it is the sister species of the highland subclade in the short corolla tube clade.…”
Section: Discussionmentioning
confidence: 99%
“…A species tree was used as input for the online INFOMAP BIOREGIONS software [ 81 ] to reconstruct the ancestral range for the P. integrifolia complex through Fitch’s method of maximum parsimony [ 82 ]. The WUSCHEL gene sequences from Segatto et al [ 25 ] were used to construct the phylogenetic tree of the Petunia species, according to the classification of Stehmann et al [ 16 ]. We used these markers because the phylogenetic tree obtained based on WUSCHEL sequences was the best supported among Petunia phylogenies and it is in agreement with previous works using nuclear and plastid markers [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Центральная роль гена WUS в регуляции идентичности и поддержании плюрипотентных стволовых клеток в апи кальной меристеме побега показана для растений разных видов (Salvini et al, 2016;Segatto et al, 2016). Экспрессия WUS ограничена группой клеток, составляющих органи зующий центр, к которому прилегают стволовые клетки (Besnard et al, 2011;Sun, Ito, 2015), а подавление его экс прессии приводит к появлению эктопических меристем, преждевременно прекращающих свое развитие (Laux et al, 1996).…”
unclassified